2016
DOI: 10.1186/s13017-016-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

Emergency abdominal surgery after solid organ transplantation: a systematic review

Abstract: AimsDue to the increasing number of solid organs transplantations, emergency abdominal surgery in transplanted patients is becoming a relevant challenge for the general surgeon. The aim of this systematic review of the literature is to analyze morbidity and mortality of emergency abdominal surgery performed in transplanted patients for graft-unrelated surgical problems.MethodsThe literature search was performed on online databases with the time limit 1990–2015. Studies describing all types of emergency abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 75 publications
1
63
2
5
Order By: Relevance
“…To support elective resection, the postoperative outcome after elective procedure was no different from that in immunocompetent patients. The often‐significant severity of sigmoid diverticulitis among transplant recipients has prompted consideration of pre‐transplant prophylactic surgery for patients with sigmoid diverticulosis proven by colonoscopy, but this is a feasible approach only for kidney transplant candidates, as patients awaiting heart, lung, or LT are generally too sick to tolerate any major surgical procedures …”
Section: Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…To support elective resection, the postoperative outcome after elective procedure was no different from that in immunocompetent patients. The often‐significant severity of sigmoid diverticulitis among transplant recipients has prompted consideration of pre‐transplant prophylactic surgery for patients with sigmoid diverticulosis proven by colonoscopy, but this is a feasible approach only for kidney transplant candidates, as patients awaiting heart, lung, or LT are generally too sick to tolerate any major surgical procedures …”
Section: Etiologymentioning
confidence: 99%
“…Although acute appendicitis accounts for over 1 million patient days of admission in the United States, incidence of acute appendicitis after LT has been reported as being very low 61,62 : 2% of abdominal surgery after LT is related to acute appendicitis. 62 However, there was a high percentage of misdiagnosis with a markedly high incidence of complicated appendicitis. Clinical presentation is similar to nonim-…”
Section: Acute Appendicitismentioning
confidence: 99%
“…Previous studies have reported that postoperative outcomes for solid organ transplant recipients following general surgical procedures are worse than the general population, with a recent review citing up to 32.7% mortality and 17.5% morbidity for emergency abdominal surgery, in comparison with 9% morbidity in nontransplant recipients . For appendectomy specifically, in the largest case series to date that included transplant recipients, there were only 17 appendectomies reported, and only 3 of those performed on KTR.…”
Section: Introductionmentioning
confidence: 96%
“…Appendicitis is one of the most common surgical diseases in the United States, with a lifetime risk of 6.7% in females and 8.6% in males . Like the general population, kidney transplant recipients (KTRs) are at risk of requiring appendectomy, although the incidence of appendicitis in KTR has not been well documented outside of small case series . Further, while post‐appendectomy morbidity is low in the general population (4.1%‐6.4%) and average postoperative length of stay (LOS) is short (0‐2.4 days), it is unknown whether risk, LOS, and, thus, hospital‐associated cost are amplified for KTR .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation